Serum amyloid P component and pro-platelet basic protein in extracellular vesicles or serum are novel markers of liver fibrosis in chronic hepatitis C patients. - Kumiko Shirai; Hayato Hikita; Sadatsugu Sakane; Ryohei Narumi; Jun Adachi; Akira Doi; Satoshi Tanaka; Yuki Tahata; Ryoko Yamada; Takahiro Kodama; Ryotaro Sakamori; Tomohide Tatsumi; et al. (PLoS ONE, 2022)
Extracellular vesicles (EVs) contain proteins, mRNAs, and microRNAs, and their cargos have emerged as novel diagnostic markers in various diseases. We aimed to discover novel and noninvasive biomarkers of liver fibrosis by proteomic analysis using serum EVs in patients with chronic hepatitis C. We performed shotgun proteomics using serum EVs isolated from 54 patients with histologically assessed liver fibrosis. Shotgun proteomics identified a total of 974 proteins, and 445 proteins were detected in more than half of the patients. Among them, a total of 9 proteins were identified as proteins that tended to increase or decrease with liver fibrosis with a significance of p<0.005 and that were different between F1-2 patients and F3-4 patients with a significance of p<0.01. Among the 9 proteins, targeted proteomics using serum EVs isolated from the sera of another 80 patients with histologically assessed liver fibrosis verified that serum amyloid P component (SAP) and pro-platelet basic protein (PPBP) levels in EVs significantly decreased with the progression of liver fibrosis and were significantly lower in F3-4 patients than in F1-2 patients. The diagnostic accuracies of SAP and PPBP in EVs for the liver fibrosis stage were comparable to those of type IV collagen 7S, hyaluronic acid, and the fibrosis-4 index (FIB-4 index). Moreover, serum SAP and PPBP levels correlated with the levels in EVs, and the ability of serum SAP and PPBP to diagnose liver fibrosis stage was also comparable to the abilities of type IV collagen 7S, hyaluronic acid, and the FIB-4 index. In conclusion, proteomic analysis of serum EVs identified SAP and PPBP as candidate biomarkers for predicting liver fibrosis in patients with chronic hepatitis C. In addition, SAP and PPBP levels in serum are strongly correlated with those in EVs and could represent markers of liver fibrosis.